Assessing Self-reported Medication Adherence in Inflammatory Bowel Disease: A Comparison of Tools. Issue 9 (September 2016) - Severs, Mirjam; Zuithoff, Peter N. P. A.; Mangen, Marie-Josée J.; van der Valk, Mirthe E.; Siersema, Peter D.; Fidder, Herma H.; Oldenburg, Bas
Abstract : Background: Capturing (non)-adherence to medical prescriptions in patients with inflammatory bowel disease (IBD) is challenging. We aimed to compare 3 different tools to measure self-assessed medication adherence of patients with IBD. Methods: Adult patients with Crohn's disease and ulcerative colitis were prospectively followed. IBD-specific medication use was collected by 3-monthly questionnaires. At 2.5 years of follow-up, medication adherence was assessed using 3 tools: (1) the 8-item Morisky Medication Adherence Scale (MMAS-8), (2) the single question how well patients take their daily medication using a Visual Analogue Scale (VAS), and (3) the Forget Medicine scale (FM), assessing how often patients forget their medication. Cross-sectional agreement among measures was visualized with scatterplots and quantified with Spearman's rank correlations. Results: In total, 913 patients with IBD were analyzed, 697 of whom received IBD-specific medication. High adherence on the MMAS-8 was consistent with high scores on the VAS and low scores on the FM. Disagreement between tools increased when patients were less adherent. A correlation of 0.44 was found between the MMAS-8 and VAS; −0.59 between the MMAS-8 and FM, and −0.55 between the VAS and FM (all P < 0.01). The VAS most optimally represented the quantitative variability of adherence, whereas the MMAS-8 and the FM might have resulted in overestimation or underestimation of adherence due to unequal differences in outcome possibilities. Conclusions: In patients with IBD, a VAS seems the most appropriate tool for quantifying medication adherence in clinical practice. The MMAS-8 may be used additionally to provide insight in specific reasons for non-adherence. Abstract : Article first published online 2 August 2016.